Forest vegetation in western Romania in relation to climate variables: Does community composition reflect modelled tree species distribution? - Heinrichs, Steffi; Walentowski, Helge; Bergmeier, Erwin; Mellert, Karl Heinz; Indreica, Adrian; Kuzyakov, Yakov; Leuschner, Christoph; Petrițan, Any Mary; Teodosiu, Marius (Marin Dracea National Research-Development Institute in Forestry, 2016)
. European beech (Fagus sylvatica L.) is the prevailing tree species of mesic forests in Central Europe. Increasing summer temperatures and decreasing precipitation, as climate change scenarios predict, may, however, negatively influence beech growth and induce a shift to more thermophilous forest communities. Temperatures as expected in the future for western Central Europe are currently found in parts of western Romania. In light of this climate analogy we investigated forest vegetation as an indicator for future vegetation changes in five regions of western Romania representing a climatic gradient. We related species composition to climate variables and examined if tree and understorey species composition respond similarly to the climatic gradient. We further analysed if tree species occurrences correspond with their modelled distance to the rear niche edge. We found evidence for climatic effects on vegetation composition among regions as well as within deciduous and pine forests, respectively. This underlines that vegetation composition is a useful indicator for environmental change. Tree and understorey species compositions were closely linked showing that community-based characterization of forest stands can provide additional information on tree species suitability along environmental gradients. Both, vegetation composition and a climatic marginality index demonstrate the rear niche edge occurrence of beech in the studied sites of Romania and can predict the site suitability for different tree species. While vegetation surveys indicate Quercus petraea to be associated to moderately mesic forests, the marginality index suggested an inner niche position of sessile oak along the climatic gradient. Phytosociological relevés that differentiate between subspecies (or microspecies) of sessile oak with differing habitat requirements should be considered to complement national forest inventories and species distribution maps when modelling rear distribution edges. We conclude that climate driven forest vegetation composition in western Romania is a suitable analogon and may indicate future forest development in western Central Europe.
Keywords: climate analogy; climate change; Fagus sylvatica; plant community; Quercus petraea; climatic marginality index; rear edge populations